IMPLEMENTATION OF THE ENGLISH PREMIER LEAGUE'S INVOLVEMENT IN CAMPAIGNING THE ANTI-RACISM MOVEMENT - Yubel, Novrel Esa; Reuspatyono, Reuspatyono (Universitas Nasional, 2022)
The issue of racism is still common, especially in the black race. Black people are often subjected to discriminatory treatment, such as violence to slurs. The death of George Floyd in 2020 adds to the dark history of racism, and this has further strengthened the campaign against the importance of anti-racism to black citizens through the slogan